FORECASTING AND DIAGNOSTICS OF PREECLAMPSIA ON PRECLINICAL STAGE (Archive of Conferences, 2021)
Preeclampsia is currently one of the leading causes of death and severe maternal morbidity. Althoughits prevalence is still underestimated in some places due to underreporting, preeclampsia is a medical conditionthat healthcare professionals need to know how to deal with and respond to. For this reason, research on a topicstays with progress in understanding it, which often implies improvements and changes in concepts andbehavior